CAN THE REQUIREMENTS OF SHARIAH LAW REGARDING CRIMINAL PUNISHMENTS BE INTERPRETED IN A WAY THAT IS COMPATIBLE WITH THE ICCPR AND CAT? - Alfitri, Alfitri (Indonesian Journal of International Law, 2021)
Criminal law deals with the protection of public interests and values deemed to be crucial for a particular society. In Islam, these values are ascribed to the divine commands. Thus, there will be calls from some Muslims for the implementation of Islamic criminal law by the state for they believe that this is required by Islam. Can therefore the death penalty or corporal punishments required by the Shariah law be imposed by a state while they are in conflict with the state’s obligation to comply with international human rights instruments? This paper will analyze this uneasy situation faced by some Muslim countries implementing Islamic criminal law but party to the ICCPR and CAT. It aims at verifying that an extreme universalism or cultural relativism approach regarding the validity of international human rights norms on this matter is insufficient. This is because Islamic doctrines strongly influence Muslims on this matter and failure to seriously engage them will lead to rejection of international human rights instruments which are important for protecting individual rights. This paper argues that an approach that is able to reconcile the requirements of Shariah law regarding criminal punishments and those of international human rights norms is necessary.